Democratic Accountability and Metropolitan Governance: The Case of South Hampshire, UK. (August 2014) - Buser, Michael
This paper examines the notion of democratic accountability through an investigation of metropolitan governance in South Hampshire, UK. The author employs an interpretive approach to trace varying readings of democratic accountability and to analyse how these notions reflect and influence specific institutional arrangements. The paper highlights how accountability can be strategically deployed to accomplish and bolster diverse policy and political objectives and how these interpretations impact the quality of democratic engagement